2014
DOI: 10.1148/radiol.14140473
|View full text |Cite
|
Sign up to set email alerts
|

CT Colonography: Clinical Evaluation of a Method for Automatic Coregistration of Polyps at Follow-up Surveillance Studies

Abstract: Purpose:To evaluate the accuracy of a method of automatic coregistration of the endoluminal surfaces at computed tomographic (CT) colonography performed on separate occasions to facilitate identification of polyps in patients undergoing polyp surveillance. Materials and Methods:Institutional review board and HIPAA approval were obtained. A registration algorithm that was designed to coregister the coordinates of endoluminal colonic surfaces on images from prone and supine CT colonographic acquisitions was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…9 Ayrıca BT kolonografi kolorektal lezyonların araştırılmasında etkin bir inceleme yöntemidir. 10,11 Biz olgularımızda 6-8 MHz frekanslı konveks probla, şüphede kaldığımız olguları 5-13 MHz'lik yüzeyel probla inceledik. Lezyonların hiperekoik homojen yapıda olduklarını ve barsak içeriğinden bu özellikleri ile kolaylıkla ayrılabildiğini, Doppler inceleme ile vaskülarite olmasının ise şüpheli görünümlerde fekal materyal ile gerçek lezyon ayrımında etkili olduğunu gördük.…”
Section: Discussionunclassified
“…9 Ayrıca BT kolonografi kolorektal lezyonların araştırılmasında etkin bir inceleme yöntemidir. 10,11 Biz olgularımızda 6-8 MHz frekanslı konveks probla, şüphede kaldığımız olguları 5-13 MHz'lik yüzeyel probla inceledik. Lezyonların hiperekoik homojen yapıda olduklarını ve barsak içeriğinden bu özellikleri ile kolaylıkla ayrılabildiğini, Doppler inceleme ile vaskülarite olmasının ise şüpheli görünümlerde fekal materyal ile gerçek lezyon ayrımında etkili olduğunu gördük.…”
Section: Discussionunclassified
“…Approaches to such registration have included using the tenaie coli as fiducial markers and finding ways to register similar haustral folds. One registration technique was evaluated in a radiologist observer trial and for coregistration of polyps at follow-up surveillance [114, 115]. Recent work has shown that the marginal artery of the colon follows the course of the tenia mesocolica and can serve as a fiducial marker for locating the colon in areas of collapse [116, 117] (Fig.…”
Section: Bowelmentioning
confidence: 99%